Friction and Wear Properties of Cold Gas Dynamic Sprayed α-Al2O3-Al Composite Coatings. (29th July 2013) - Wu, Jie; Tao, Yongshan; Jin, Huazi; Li, Ming; Xiong, Tianying; Sun, Chao
Abstract : Different proportions of α -Al2 O3 and pure Al powders were coated onto AZ91D magnesium alloy substrates by cold gas dynamic spray. The microstructure and morphologies of the coatings were observed by scanning electron microscope. The friction and wear properties were tested by a ball-on-disk wear tester. It was found that the interfaces between grains and substrates formed close boundaries. It is revealed that the composite coatings could increase the friction or wear properties of the coatings. It was observed that the wear of coatings was converted from adhesive wear into abrasive wear with α -Al2 O3 particles increasing and that the adhesive wear accompanied with abrasive wear would increase the wear rate of coatings.